Informative Combat of the Russian Hybrid War - Bînă Marian-Valentin; Dragomir Cristian (Scientific Bulletin, 2020)
The objective of this paper is to analyze the control system that the media offered to Russian disinformation campaigns in a supposed context of hybrid warfare. The exposure of the news offered by the main media channels allows the analysis of the concept of hybrid warfare to be concentrated and its comparison with the traditional strategic conception, in order to determine if the activities in question can be classified in this type of conflict. Information warfare and related components such as cyber warfare, electronic warfare and more, are becoming increasingly complex and can be used both defensively and offensively in the current security context offered by the national media.